2007
DOI: 10.1111/j.1365-2850.2007.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported care needs of outpatients with a bipolar disorder in the Netherlands

Abstract: The care needs of patients with a bipolar disorder have not been studied to date. In the present research, the care needs, care received and unmet care needs for a population of outpatients with a bipolar disorder in the Netherlands are described. The participants (n = 157) completed the Need for Care Questionnaire and a questionnaire addressing various demographic and clinical characteristics. The results show the care needs to mainly involve the domains of psychological help, psychiatric help and social func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…The proportion of met vs unmet needs and the types of unmet needs in this study were very similar to several Indian studies, which have assessed health-care needs among patients with severe mental illnesses including schizophrenia and BD[18,22,25,29-31]. The pattern of primacy of economic and welfare needs in Indian studies is also quite unlike the pattern of needs reported in Western studies, where a greater amount of help and benefits are usually received from health-care services; therefore, social needs are more often unmet than economic, welfare or treatment needs[7,24,32-35]. These differences clearly reflect the inadequate support that patients receive from formal health-care services in India, which forces them to turn to their family and friends to fulfil their needs[18,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of met vs unmet needs and the types of unmet needs in this study were very similar to several Indian studies, which have assessed health-care needs among patients with severe mental illnesses including schizophrenia and BD[18,22,25,29-31]. The pattern of primacy of economic and welfare needs in Indian studies is also quite unlike the pattern of needs reported in Western studies, where a greater amount of help and benefits are usually received from health-care services; therefore, social needs are more often unmet than economic, welfare or treatment needs[7,24,32-35]. These differences clearly reflect the inadequate support that patients receive from formal health-care services in India, which forces them to turn to their family and friends to fulfil their needs[18,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Another research field focuses on care needs of outpatients with BD (Goossens, Knoppert-Van der Klein, Kroon & Van Achterberg, 2007), showing that the needs were mainly to be found in the areas of psychological help, psychiatric help and social functioning. The data in the study by Goossens et al (2007) was collected by using a survey technique with fixed questions.…”
Section: Introductionmentioning
confidence: 99%
“…The data in the study by Goossens et al (2007) was collected by using a survey technique with fixed questions. Existential issues were not in focus.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of access to such services probably adversely influences the overall long-term outcome (Morgan et al, 2005; Goossens et al, 2007). …”
Section: Unmet Needs Identified In the Literature (Summarized In Tmentioning
confidence: 99%